Elasto-Plastic Analysis of 3D Frames with Generalized Yield Function - Singh, Harpal (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Three dimensional three node elasto-plastic finite element has been presented. Hinges have been assumed to form at the points of integration (Gauss points) which are distributed over the length of the element. One integration point at the center and the other two near the ends. The inelastic interaction between biaxial bending moment, torque and axial force has been considered by means of generalized yield interaction surface and a flow rule with strain hardening has been associated. The element is more effective where the location of hinges is not known in advance. The concept has been applied successfully on three dimensional steel and reinforced concrete frames